Application of Satellite Remote Sensing on the Detection of Algal Blooms by Drs. B. Greg Mitchell and Mati Kahru Presented in Training Course on Remote Sensing of Algal Blooms in the sea, April 7-10, 1999, Hong Kong, China - Asia Pacific Economic Cooperation, Marine Resources Conservation Working Group; Chinese Taipei, Environmental Protection Administration; USA, Ubiversity of California, San Diego (Hong Kong, China APEC Secretariat, 1999)
Summary on booklet cover
CD 1 - Ecopsychology of Harmful Algae Taxa and Principles of Ocean Optics and Ocean Color Algorithm Case Study, CD 2 - Ocean Optics Instrumentation and Applications and Measurements of Ocean Optical Properties & Data Processing, CD 3 - Basic of Image Analysis and Applications1 (Principles of Digital Imaging, Basic operations on images, Image file formats, Getting satellite data), CD 4 - Basic of Image Analysis and Applications 2 (SeaWiFS products, SeaDAS, Algorithms for detecting red tides, Case study)
Title on booklet cover
Keywords: Algal Blooms Detections -- Remote Sensing; Remote Sensing Systems -- Training Course -- China